Prognostic value of ZAP‐70 expression in chronic lymphocytic leukemia as assessed by quantitative polymerase chain reaction and flow cytometry. Issue 2 (8th November 2013) - Adams, Rebecca L. C.; Cheung, Catherine; Banh, Raymond; Saal, Russell; Cross, Donna; Gill, Devinder; Self, Marlene; Klein, Kerenaftali; Mollee, Peter
<x xml:space="preserve">Abstract</x> Background Chronic lymphocytic leukemia (CLL) is a disorder in which the tempo of disease progression is highly variable, and prognostic markers that can be utilized at diagnosis are regarded as clinically important. Currently, there are several prognostic factors, such as immunoglobulin heavy chain (IgVH) mutational status, and ZAP‐70 protein expression in neoplastic B‐cells, that have demonstrated significant discriminative power in the prognostication of CLL. They are, however, largely unavailable in the routine diagnostic laboratory setting. Methods In this study, we characterized the IgVH status and ZAP‐70 expression by molecular techniques in a cohort of 108 patients with CLL, and correlated these results with three different methods of ZAP‐70 expression by flow cytometry. We then assessed the results of these methods in terms of prognostic power as characterized by time to first treatment (TTFT). Results By comparing three different flow cytometry methods using receiver–operator curve (ROC) analysis, we identified that by utilizing a corrected mean fluorescence intensity (CorrMFI) algorithm for assessing ZAP‐70 expression, there was good correlation with both IgVH mutational status, and ZAP‐70 expression as assessed by qPCR. We were also able to show that ZAP‐70 expression, as assessed by both qPCR and the CorrMFI method, was prognostic of TTFT. Conclusions While confirmation in a larger patient cohort, with longer follow‐up is required, we believe that the CorrMFI represents the most promising method currently available in a routine diagnostic setting for the assessment of ZAP‐70 expression in CLL patients. © 2013 International Clinical Cytometry Society